A new gypsicolous species of Launaea (Asteraceae, Cichorieae) from north Somalia - Baldesi, Giacomo; Kilian, Norbert (Phytotaxa, 2021)
Launaea calmadowensis from Saanag Region in north Somalia is described as a species new to science and illustrated, based on a single gathering known from a hitherto unidentified part of a collection made by R. Bavazzano & J. J. Lavranos in 1970/71 and preserved at FT Herbarium. It is inferred from the comparison of diagnostic morphological characters that this species from gypsaceous hills belongs to the L. angustifolia group of L. sect. Zollikoferia and is most closely related to the North African L. quercifolia.